A Feasibility study on hand-blown glass products - Atienza, Maria Jazmin; Erpelo, Michael; Galon, Jude Hercules M.; Santos,Michelle (College of Engineering, 2000)
The Material and Science Department (MSD) of the Department of Science and Technology (DOST) has developed a new technology in glass manufacturing. The hand-blown glass products use broken glass cullets and lahar glass as its raw materials. Raw materials are melted then blown manually to form creative glass products. The outputs were named babASHagin products by the proponents of the study. The market competitor analysis, which included examinations of the industry, competitor, demand, and supply data yielded the following market share and sales plan for babASHagin products. Furthermore, the Market Study identified households, hotels and restaurants, export market and wine manufacturers as the company?s target customers. A comprehensive marketing strategy totaling P1,113,341.00 for the first five year of operations. In the Technical Study, the group was able to gather much needed information regarding the processes, operations and projected costs of all relevant technical inputs needed to produce Hand-Blown Glass Products. Processes involving the manufacture of the said glass products were patterned from current industry practices. Machine evaluation was done to come up with the most suited type of machine for the company?s purposes. Raw materials, machine and labor requirements were determined and an optimal production plan was devised based on these said factors. Workers will work 8 hours a day, 5 days a week. A team type of schedule, comprised of two (2) teams, was adopted due to the hazards brought about by working in high temperature areas. One (1) additional machine and four (4) more laborers will be added to meet the increasing demand of years 2 to 5. A plant site evaluation was also conducted to determine the best site to put up the plant. An evaluation whether to lease or buy was conducted and it was conducted that it would be more cost effective if the company would lease a land and existing structure. An evaluation of the possible plant sites was done taking into consideration the following criteria: location of suppliers, customers, infrastructure, population density and land rate. The babASHagin Works manufacturing facility will be a 1000 spare meter land at 45 Arthuro Drive, Bo. Bagumbayan, Taguig. Leasing the site will cost the company P95,000.00 per month and an additional P3,291,000.00 retro-fitting cost was incurred in modifying the existing building to suit the company?s needs. The Total Project cost for the first 12 months of operation is determined to be P16,693,452.96. Organization and Management Study indicated that the corporation-type is the best form of ownership for the company. Relevant features of this type of ownership include entity, life, liability, pooling of capital, pooling of management talents and business contacts, attraction of loan financing, and business growth. In addition, 18 various managerial and staff positions were assigned based on the minimum company needs. Salaries were determined based on industry standards. Salaries increase by 10% annually. For the Financial Study, the company has identified an initial total project cost, which is based in a one-year start-up cost of the project. The company will be loaning 40% of its capital, or P 6,700,000.00 from the Philippine National Bank. This loaning agent was chosen for the following reasons: loan amount, interest rate, willingness to lend, payment period and flexibility of terms. The company will be offering capital stock worth 60% of its initial capital requirements, or P 10,000,000. There would be 500,000 shares of capital stock worth P20.00 each. Using sensitivity analysis and financial ratios, the project was assessed at MARR = 40%. It was concluded that it is financially feasible. Its payback period is 9.8 months, and its IRR is 57.57%, and its net present value is calculated at P 22,283,471.68. In conclusion, the Social Profitability Study yielded several benefits that the company would effect. Benefits include recycling of local raw materials, no toxic waste generated and flexibility in shifting to natural gas. Employment of 37 employees will also be generated for the first year. For the local industry, the purchase of raw materials worth P 1,449,760.94 and office and plant supplies worth P 6,620,346.17 will be earned for the first year. Lastly, the government will gain additional revenue through corporate income tax totaling P 5,003,444.85. Collection of withholding taxes equals to P 425,181.99. these are values for the first year alone and are increasing for the projected life of the company.